Effects of Co-culture on Improved Productivity and Bioresource for Microalgal Biomass Using the Floc-Forming Bacteria Melaminivora Jejuensis - Kim, Dong-Hyun; Yun, Hyun-Sik; Kim, Young-Saeng; Kim, Jong-Guk (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial and algal floc formation was induced by inoculating three species of wastewater-derived bacteria (Melaminivora jejuensis, Comamonas flocculans, and Escherichia coli) into algal cultures (Chlorella sorokiniana). Bacterial and algal flocs formed in algal cultures inoculated with M. jejuensis and C. flocculans, and these flocs showed higher sedimentation rates than pure algal culture. The floc formed by M. jejuensis (4988.46 ± 2589.81 μm) was 10-fold larger than the floc formed by C. flocculans (488.60 ± 226.22 μm), with a 3-fold higher sedimentation rate (M. jejuensis, 91.08 ± 2.32% and C. flocculans, 32.55 ± 6.33%). Biomass and lipid productivity were improved with M. jejuensis inoculation [biomass, 102.25 ± 0.35 mg/(L·day) and 57.80 ± 0.20 mg/(L·day)] compared with the productivity obtained under pure algal culture conditions [biomass, 78.00 ± 3.89 mg/(L·day) and lipids, 42.26 ± 2.11 mg/(L·day)]. Furthermore, the fatty acid composition of the biomass produced under pure algal culture conditions was mainly composed of C16:0 (43.67%) and C18:2 (45.99%), whereas the fatty acid composition of the biomass produced by M. jejuensis was mainly C16:0 (31.80%), C16:1 (24.45%), C18:1 (20.23%), and C18:2 (16.11%). These results suggest the possibility of developing an efficient method for harvesting microalgae using M. jejuensis and provide information on how to improve biomass productivity using floc-forming bacteria.